Interior Galeri Kebaya Indonesia di Surabaya - Chandra, Cheung Vivi (Intra, 2014)
Interior Design Indonesian Gallery ofÂ  Kebaya in Surabaya , itâs purposeÂ  is to facilitate the public. The gallery where there is a museum that promotes the historical value of kebaya from time to time. It also provides public area likes, restaurant / cafÃ©, to enhance the comfort of visitors. This gallery itself was designed theme with the concept called âComplexityâ which is describe the difficulty and the beauty ofÂ  kebaya and re-live in this modern era. Spiral has been modified more simple become circle form., and apllied in layout, furniture, even elements in interior.Â